Drying Characteristics of Shrimp Head Waste - Kumar, Pallaw; S., Bandyopadhyay (Fishery Technology, 2025)
Drying characteristics of shrimp head waste were studied under constant drying conditions with an objective of obtaining rate and design data for the drying process. Experiments were conducted with the whole shrimp head waste and the head waste without shell at dry bulb temperatures of 50, 60 and 70CC, keeping relative humidity at 40% and drying air velocity at 1.965 m/s. Results showed that the shell cover hindered the drying process considerably and the head waste without shell required less time to dry under a particular drying condition. There was no constant rate period during drying of samples without shell. Both constant and falling rate periods were observed in the whole head drying. Drying of both types of sample would be preferable at 70oC air temperature.